Intermolecular bonding in water clusters from the molecular-wide and electron density-based (MOWED) perspective : a theoretical study - Cukrowski, Ignacy (University of Pretoria, 2024)
Dissertation (MSc (Chemistry))--University of Pretoria, 2023.